Metabolic consequences of erastin-induced ferroptosis in human ovarian cancer cells: an untargeted metabolomics study - Kirkwood-Donelson, Kaylie I.; Jarmusch, Alan K.; Bortner, Carl D.; Merrick, Bruce Alex; Sinha, Birandra K. (Frontiers in Molecular Biosciences, 2025)
IntroductionOvarian cancer has been difficult to cure due to acquired or intrinsic resistance and therefore, newer or more effective drugs/approaches are needed for a successful treatment in the clinic. Erastin (ER), a ferroptosis inducer, kills tumor cells by generating and accumulating reactive oxygen species (ROS) within the cell, resulting in an iron-dependent oxidative damage-mediated ferroptotic cell death.MethodsWe have utilized human ovarian cancer cell lines, OVCAR-8 and its adriamycin-selected, multi-drug resistance protein (MDR1)-expressing NCI/ADR-RES, both equally sensitive to ER, to identify metabolic biomarkers of ferroptosis.ResultsOur studies showed that ER treatment rapidly depleted cellular glutathione and cysteine and enhanced formation of ophthalamate (OPH) in both cells. Opthalalmate has been proposed to be a biomarker of oxidative stress in cells. Our study also found significant decreases in cellular taurine, a natural antioxidant in cells. Additionally, we found that ER treatment decreased cellular levels of NAD+/NADP+, carnitines and glutamine/glutamate in both cells, suggesting significant oxidative stress, decrease in energy production, and cellular and mitochondrial disfunctions, leading to cell death.ConclusionOur studies identified several potential biomarkers of ER-induced ferroptosis including OPH, taurine, NAD+, NADP+ and glutamate in ovarian cancer cells. Identifying specific metabolic biomarkers that are predictive of whether a cancer is susceptible to ferroptosis will help us devise more successful treatment modalities.